Luxembourg : Financial Sector Assessment Program: Technical Note-Macroprudential Framework And Policies. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2017)
This Technical Note discusses the findings and recommendations made in the 2017 Financial Sector Assessment Program for Luxembourg in areas of macroprudential framework and policies. Luxembourg has a large financial system that contributes a significant share of GDP and is globally interconnected. The institutional arrangement is broadly appropriate for effective macroprudential policy, but some areas should be strengthened. The monitoring and analysis of systemic risks by the Banque Centrale du Luxembourg is appropriate and performed on a timely basis. The authorities are encouraged to continue to increase efforts to monitor risks related to the investment fund industry.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet